The Performance effects of outcome-based incentive pay plans on sales organizations: A contextual analysis - (:unkn) unknown (My University, 2003)
The contextual role of sales volatility, the complexity of customers’ purchase decisions, and the level of monitoring on the performance impact of incentives are examined. Results reveal that the use of an incentive plan is positively related to all three dimensions of organizational performance. This relationship is moderated positively by the customers’ purchase decisions and negatively by sales volatility and monitoring. In addition, the contextual role of sales volatility, the complexity of customers’ purchase decisions, and the level of monitoring differ according to the performance measure used. Implications of the findings are presented, followed by limitations and future research directions. © 2003 PSE National Educational Foundation. All rights reserved.